Growth of 2, 2-Biimidazole-Based Nanorods on Mica Substrate. (12th December 2010) - Sowwan, Mukhles; Abul Haj, Mohammad; Faroun, Maryam; Hawash, Zafer; Ghabboun, Jamal; Rida, Alaa; Karmi, Abeer; Sultan, Wadie; Husseini, Ghaleb A.
Abstract : The synthesis of a one-dimensional single-stranded helix using the crystallization of silver (I) nitrate and 2, 2-biimidazole has promising potential for use in the area of nanotechnology mainly because of its unique electrical properties and its structural similarity to naturally occurring nucleic acids. In this study, we report a new method for the deposition and growth of 2, 2-biimidazole-based nanorods on mica substrates by employing a complex solution of silver nitrate (I) and 2, 2-biimidazole. The morphology and electrical polarizability of the prepared nanorods are investigated by tapping mode atomic force microscopy (AFM) and noncontact electrostatic force microscopy (EFM). The experimental results show highly polarizable and singly separated nanorods oriented in three preponderant directions. In addition, we show that the active K + ions on the mica surface are required for the formation of these nanorods. Additionally, these potassium ions are a critical factor in controlling the nucleation and morphology of nanostructures.